INFLUENCE CO-CREATION VALUE, DESTINASTION IMAGE, AND THE FLEXIBILITY OF TOURISM PACKAGES ON TOURISTS' DECISIONS TO VISIT BONJERUK TOURIST VILLAGE - Ahmad Riki Kadri Budiman; Akhmad Saufi; Dwi Putra Buana Sakti; Mahyuni, Mahyuni; Hairil Anwar (Bajang Institute, 2025)
This research aims to analyze the influence Value Co-Creation, Destination Image, and Flexibility of Tour Packages on tourists' visiting decisions in the Bonjeruk Tourism Village, with Tourist Preferences as a moderating variable. The approach used in this research is quantitative, where data is collected through distributing Likert scale questionnaires online to tourists who have visited the Bonjeruk Tourism Village, using the technique purposive sampling. The collected data is then analyzed using statistical calculations to test the relationship between variables. The research results show that Value Co-Creation And Destination Image has a significant positive influence on tourists' visiting decisions. Although Tour Package Flexibility can be considered an added value, this variable does not show a significant influence on visiting decisions, which may be due to the dominance of other factors such as tourist attraction and destination image. In addition, Tourist Preferences have been proven to moderate the influence Destination Image on the decision to visit, but did not have a significant effect in moderating the relationship between Value Co-Creation and Flexibility of Tour Packages on visiting decisions. This finding proves and provides novelty to previous research Destination Image proven to have a significant positive influence on tourists' visiting decisions, both directly and after being moderated by Tourist Preferences. Meanwhile, though Value Co-Creation has a positive role, Tourist Preferences are not able to moderate its influence on visiting decisions. This research also provides a practical contribution where the results of this research can be used by tourism village managers as a reference for designing more effective marketing strategies